2023
DOI: 10.1128/aem.01744-22
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Quaternary Ammonium Compound-Based Antimicrobial Coating Used in Public Transport during the COVID-19 Pandemic

Abstract: This study evaluated the performance of a commercially available antimicrobial coating that was used by the transport industry in the United Kingdom during the COVID-19 pandemic. While the product was effective against ɸ6, the efficacy of the coating depended upon the material to which it was applied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…While samples were taken before daily terminal cleaning, high bacterial levels demonstrate the ease with which passengers contaminate the environment. We previously showed that when Zoono was used to coat a range of materials relevant to public transport, the deposition of organic debris severely reduced its virucidal efficacy against ɸ6 (a surrogate for SARS-CoV-2) (Aranega-Bou et al, 2023). As part of the same study, we found that Zonitise, when applied to stainless steel or polystyrene test surfaces, was ineffective against ɸ6 even in the absence of organic debris (previously unpublished data, supplementary table 2).…”
Section: Discussionmentioning
confidence: 99%
“…While samples were taken before daily terminal cleaning, high bacterial levels demonstrate the ease with which passengers contaminate the environment. We previously showed that when Zoono was used to coat a range of materials relevant to public transport, the deposition of organic debris severely reduced its virucidal efficacy against ɸ6 (a surrogate for SARS-CoV-2) (Aranega-Bou et al, 2023). As part of the same study, we found that Zonitise, when applied to stainless steel or polystyrene test surfaces, was ineffective against ɸ6 even in the absence of organic debris (previously unpublished data, supplementary table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of transmission from a brief contact with a single contaminated surface is generally low, however, as individuals are in contact with multiple contaminated surfaces, the population density is high, the duration of a stay in an existing location increases, and the effectiveness of mitigation measures is poor (e.g. surface cleansing and handwashing), the risk of infection's transmission escalates [ 1 ]. Pathogen transmission is not limited to healthcare settings like hospitals or medical centres.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogen transmission is not limited to healthcare settings like hospitals or medical centres. It can also occur in community spaces such as public transportation, where numerous individuals come into contact with various surfaces such as seats, doorknobs, railings, tables, and armrests [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%